Novel cellulose nanofibers/barium titanate nanoparticles nanocomposites and their electrical properties. (23rd September 2018) - Hassan, Mohammad L.; Ali, Ashraf F.; Salama, Aliaa H.; Abdel‐Karim, Amal M.
Abstract: Green nanocomposite films from cellulose nanofibers/barium titanate (CNF/BT) with high homogeneity were successfully prepared by doping different ratio of BT nanoparticles (2.5 to 25 wt%) into CNF. Scanning electron microscope images showed homogenous distribution of BT in the CNF matrix. Thermogravimetric analysis results showed good thermal stability of the prepared nanocomposites. X‐ray diffraction analysis showed that the tetragonality of BT grains was retained in the composite samples. Addition of BT nanoparticles to CNF resulted in decreasing the tensile strength properties of the films. The dielectric properties were analyzed in detail with respect to frequency ranged from 0.1 Hz to 5 MHz, temperature ranged from 289 to 373 K, and BT loading. The high k values of the CNF/BT films were attributed to spontaneous polarization of BT particles. The dielectric constant of the nanocomposites increased by addition of BT nanoparticles up to 5 wt% and decreased afterwards. Hopping ionic conduction was proved as a conduction mechanism of the prepared nanocomposites. The activation energy of the conduction ranged from 0.4 to 0.08 eV. Moreover, the values of activation energy decreased as the doping level of BT nanoparticles increased. Abstract : Cellulose nanofibers (CNFs) isolated from bagasse pulp were used with barium titanate (BT) nanoparticles to make flexible film by casting. The films have high homogeneity and showed interesting electrical properties that make them having potential for flexible electronics applications.